Introdution to philosophy - Zulueta, Francisco M. (Mandaluyong City, 2010)
This book was conceived and written to meet the need for a textbook in Philosophy, which is designed for Filipino college students. It has developed out of the author's interest and experience in teaching the subject for many years. It is his belief that students and teachers of the discipline long for materials and literature written in the language which can easily be understood. Moreover, there seems to be a dearth of textbooks in Philosophy for Filipino students since foreign authors, notwithstanding their prohibitive cost, write most Philosophy books available in our libraries and in the market. This book attempts to provide the students, teachers and other readers with the necessary knowledge about philosophy to stimulate their interest and to apply their knowledge to more meaningful life experiences. The organization and content of this book basically covers important insights and information that focus on the philosophical thoughts of certain prominent personalities in the field of philosophy. It touches on the adventure of the greatest minds in history into the greatest ideas and the most complex systems of thoughts that have been evolved by human intelligence and aspirations. The author's main concern is to show that philosophy has the most direct and important bearing and relevance to men's lives and that understanding of its meaning will undoubtedly contribute immensely to their well-being. Indeed, this is the function of philosophy as a discipline: to explore the nature of man, society and the universe. This is the splendid and exciting story of man's quest for the profound mysteries of human existence
Keywords: Philosophy